Status and Benefits of Renewable Energy Technologies in the Rural Areas of Ethiopia: A Case Study on Improved Cooking Stoves and Biogas Technologies - Yitayal Addis Alemayehu (International Journal of Renewable Energy Development, 2015)
The majority of Ethiopia’s people (85%) reside in rural areas, deriving their livelihood from agriculture. Ethiopia’s energy system is characterized mainly by biomass fuel supply, with households being the greatest energy consumers. The household sector takes up nearly 94 % of the total energy supplies. Access to energy resources and technologies in rural Ethiopia is highly constrained which makes the energy supply and consumption pattern of the country to show many elements of un-sustainability. The concern on cooking practices, household economics, health, forest and agricultural resource management, and global greenhouse gas emissions has emerged as a transformative opportunity to improve individual lives, livelihoods, and the global environment. More decentralized renewable energy projects could play an important role in mitigating traditional biomass fuel use. Improved cooking stove (ICS) dissemination projects have been launched involving the private sector in the production and commercialization of the stoves. In doing so, about 3.7 million ICSs have been disseminated in the country so far which benefited stove users, producers and the total environment as about 30 million hectare of forest per year can be conserved. Conversion of animal waste to biogas energy to replace traditional fuel and use of the slurry as a fertilizer is the other current focus of the government of Ethiopia and installed more than 860 biogas digesters. The benefits obtained from these technologies are considerable and promising. However, the programs are not that much benefited the rural households where it had been intended to address. So, due attention should be given for those of the rural households in order to address the fuel wood crisis, environmental degradation and their health condition.